"Особисто я розстріляв 702 контрреволюціонера..." (реконструкція біографії чекіста Михайла Віхмана) - Бажан, О.; Золотарьов, В. (Краєзнавство, 2017)
Опираючись на архівні матеріали, вперше детально відтворено основні етапи життя співробітника радянських органів держбезпеки Михайла Мойсейовича Віхмана, його роль в утвердженні радянського режиму на Півдні України, Криму, Поволжі, функціонуванні більшовицької таємної поліції. Based on archival materials, for the first time there are reproduced in detail the main stages of the life of
MykhailoMoiseievych Vikhman, his role in the establishment of the Soviet regime in the south of Ukraine, the Crimea,
the Volga region, and the functioning of the Bolshevik secret police. The author used the documents of the Branch
State Archive of the Security Service of Ukraine, the Central State Archives of Public Associations of Ukraine, which
help to depict a portrait of Soviet state security agencies employee the against the background of the era. The article
contains detailed information on the structure of the bodies of the VUCHK-DPU-NKVD, orders that M. Vikhman
was guided, information about some checkists from his nearest environment. Reproducing the biography of Mykhailo
Vikhman, the authors of the publication were willing to uncover the repressive and punitive policies of Soviet power
in Russia and Ukraine under the conditions of the policy of war communism, the NEP, collectivization. Particular
attention is paid to the specifics of regional peculiarities, to the direct performers of these repressive actions. Опираясь на архивные материалы впервые детально воспроизведены основные этапы жизни
сотрудника НКВД Михаила Моисеевича Вихмана, его роль в становлении советского режима на Юге
Украины, в Крыму, Поволжье, функционировании большевицкой тайной полиции.